THE CORRELATION BETWEEN PHONOLOGICAL AWARENESS AND WORD LEARNING - Teresa Ravenska; Lanny Hidajat (Universitas Katolik Indonesia Atma Jaya, 2011)
This is a preliminary study to investigate the possible relationship between phonological awareness and word learning. The subjects of this study were 18 elementary students in the second grade. The subjects were first given three phonological awareness tests to measure their level of phonological awareness. Based on the results of the phonological awareness tests, the subjects were divided into the high and low phonological awareness groups. Afterwards, the subjects in both groups were taught 10 new words, followed by a vocabulary test to examine their ability in learning the new words. The results of the vocabulary test showed that the high phonological awareness group performed slightly better than the low phonological awareness group. This finding supports the assumption that L2 learners’ ability to learn L2 vocabularies is affected by their phonological awareness. Keyword: Phonological Awareness, Word Learning